Intranuclear localization of snRNP antigens (The Rockefeller University Press, 1986)
Anti-Sm antibodies recognize a group of small, nuclear RNA-protein complexes (snRNPs) containing U1, U2, U4, U5, and U6 snRNAs. Anti-RNP antibodies only react with U1 snRNA-containing complexes. The intranuclear distribution of snRNP particles was studied by double immunofluorescence staining of human fibroblasts. Mouse monoclonal anti- Sm antibodies and polyclonal patient sera reacting with different peptides in the snRNP complexes were used. The immunofluorescence patterns obtained with fluorescein isothiocyanate-conjugated anti-mouse Ig and tetramethylrhodamine isothiocyanate-conjugated anti-human Ig second antibodies were examined using computer analysis of digitized images. With this approach the similarity of different patterns could be visualized and estimated with mathematical methods. It was found that human anti-Sm serum as well as three different anti-RNP sera produced speckled patterns overlapping with the anti-Sm monoclonal pattern. Thus, Sm antigenic intranuclear domains also reacted with anti- RNP antibodies, suggesting a high degree of co-localization of the antigenic structures. A partial overlap was found between speckles detected by mouse anti-Sm antibodies and a human La-antiserum. No significant co-localization occurred between speckles detected by mouse anti-Sm antibodies and speckles detected by human antisera reacting with Scl-70 and centromeric antigens. As the U1 snRNP complex is believed to play a role in the splicing of RNA polymerase II transcripts, it appears that the speckles detected by Sm and RNP antibodies may be regions of hnRNA synthesis and mRNA processing. Although no function has been demonstrated for the U2, U4, U5, and U6 snRNPs, the co-localization with the U1 RNA complexes shown in this report indicate that they too participate in some aspect of mRNA processing. The results suggest that computer-assisted analysis of nuclear immunofluorescence patterns will be a useful tool in studies of the spatial and functional organization of the interphase nucleus.